2024
DOI: 10.1101/2024.01.29.577888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

West Nile virus is transmitted within mosquito populations through infectious mosquito excreta

Rodolphe Hamel,
Quentin Narpon,
Idalba Serrato-Pomar
et al.

Abstract: Understanding transmission routes of arboviruses is key to control their epidemiology and global health burden. Using West Nile virus and Culex mosquitoes, we tested whether arboviruses are transmitted through mosquito excreta. First, we determined the presence of infectious virions in excreta and quantified a high concentration of infectious units per excreta. Second, we showed that virion excretion starts early after oral infection and remains constant for a long period, regardless of mosquito infection leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…In addition to arboviruses capable of infecting both vertebrate and invertebrate cells, the mosquito virome (viral part of the microbiota) also contains a large proportion of viruses which can only infect vertebrate cells and are referred to as Insect Specific Viruses (ISVs) [11]. The main mechanism of transmission and maintenance of ISVs is through vertical transmission (from an infected female mosquito to their offspring) [13], although recent research has suggested another 2 potential mechanism for virus transmission, which is through mosquito excreta [12][13][14].. ISVs being transferred from mosquito generation to generation in a particular mosquito population for a period of time are referred to as the "core virome", a clear quantitative definition is currently lacking [15]. Although the exact mechanism of microbial interactions is not fully understood, ISVs such as Phasi Charoen-like virus (PCLV), Palm Creek virus and bacteria such as Wolbachia have been hypothesized to modulate their mosquito host with respect to vector competence for important arboviruses such as West Nile virus (WNV), Dengue Virus (DENV), Zika virus (ZIKV) [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to arboviruses capable of infecting both vertebrate and invertebrate cells, the mosquito virome (viral part of the microbiota) also contains a large proportion of viruses which can only infect vertebrate cells and are referred to as Insect Specific Viruses (ISVs) [11]. The main mechanism of transmission and maintenance of ISVs is through vertical transmission (from an infected female mosquito to their offspring) [13], although recent research has suggested another 2 potential mechanism for virus transmission, which is through mosquito excreta [12][13][14].. ISVs being transferred from mosquito generation to generation in a particular mosquito population for a period of time are referred to as the "core virome", a clear quantitative definition is currently lacking [15]. Although the exact mechanism of microbial interactions is not fully understood, ISVs such as Phasi Charoen-like virus (PCLV), Palm Creek virus and bacteria such as Wolbachia have been hypothesized to modulate their mosquito host with respect to vector competence for important arboviruses such as West Nile virus (WNV), Dengue Virus (DENV), Zika virus (ZIKV) [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%